P644 Impact of Postoperative Treatment with Immunomodulators and Anti-TNFα agents on long-term Reoperation Rate in ileocaecal Crohn's Disease. (21st January 2022) - Aratari, A; Scribano, M L; Baccolini, V; Pugliese, D; De Biasio, F; Verna, S; Morretta, C; Armuzzi, A; Festa, S; Papi, C
Abstract: Background: Several observations suggest that immunomodulators (IMMs) and anti-TNFα agents can affect long-term clinical course of Crohn's disease (CD). However, no convincing surgery-sparing direct effect of these medications has been demonstrated in large population-based studies. Failure to optimize these treatments, particularly a limited use in early disease course, may explain the underperformance of these strategies in the clinical practice setting. Early introduction of IMMs/anti-TNFα in CD after surgery, either as prevention of recurrence or as treatment of early endoscopic recurrence, has become a common clinical practice and may represent a surrogate model of early treatment. The aim of the present study was to evaluate the impact of IMMs/anti-TNFα on the long-term post-operative course after ileocaecal resection in CD patients. Methods: All adult CD patients who underwent their first ileocaecal resection at three major referral Centers in Rome were retrospectively reviewed. Demographic and clinical characteristics were recorded: gender, age at the time of surgery, CD behaviour (penetrating or non-penetrating), previous treatment with IMMs/anti-TNFα, and time to prescription of IMMs/anti-TNFα after surgery. The primary endpoint was the need for second resection. Statistical analysis. The Kaplan–Meier survival method was used to estimate the cumulative probability of first prescription of IMMs/anti-TNFα after surgery and to estimate the post-operative course free from reoperation. Cox proportional hazards regression model was used to assess the association of clinical variables with time to reoperation. Results: surgery: cohort 1 (1980–1998; n.198); cohort 2 (1999–2009; n.218); cohort 3 (2010–2020; n.241). The mean follow-up after surgery was 83 + 41 months. The cumulative probability of receiving IMMs/anti-TNFα after surgery was significantly different between the three cohorts but the probability of a postoperative course free from reoperation was not (figure). In the multivariate analysis, treatment with IMMs/anti-TNFα prior to the first resection (HR 9.15; 95%CI 2.77–30.21) and post-operative therapy with IMMs/anti-TNFα (HR: 0.24; 95%CI 0.07–0.74) were associated to the risk of reoperation. However, these associations had a time-varying effect and become not significant after 5 and 2 years after surgery respectively. Overall, 283 patients received IMMs/anti-TNFα at any time after surgery. Comparing early treatment (within 1, 2 or 3 years after surgery) with late treatment, no difference was observed in the cumulative risk of reoperation within 10 years Conclusion: The increasing use of IMMs/anti-TNFα agents in the post-operative setting may have little impact on the long-term reoperation rate.